PENATALAKSANAAN HOLISTIK DEMAM BERDARAH DENGUE GRADE 1 PADA ANAK USIA 2 TAHUN MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH PUSKESMAS GEDONG AIR - Efrans Caesar; Intan Nanda Rezeki; Sahab Sibuea (Majority, 2023)
Dengue hemorrhagic fever (DHF) is an acute viral disease caused by the dengue virus, characterized by a fever lasting 2-7 days, bleeding, such as nosebleeds and red spots on the skin, body (ptechiae), bleeding gums, decrease in the number of platelets, form of hemoconcentration in the form of plasma discharge and such signs as increased hematocrite, ascites, pleural effusion. Implementation of GP services through identification of risk factors, clinical problems and patient management in family-centred, patient-centred in the study focus to family centered because the patient is 2 years old and community-centred evidence-based medicine. The study conducted is a case report with the purpose of management to increase the knowledge of the family about patient disease. Primary data were obtained through history, medical examination and home visits. Secondary data were obtained from the health reports of the patient. The assessment is based on a comprehensive diagnosis of the beginning, process and end of the study quantitatively and qualitatively. The patient is a girl with complaints of fever for 3 days. Complaints of fever followed by weakness, bleeding gums accompanied by nausea and vomiting. The diagnosis and treatment are made according to the latest theories and journals. After the intervention, clinical symptoms decreased and the awareness of patients and their families increased. The diagnosis of DHF in this patient was consistent with the theory of several guidelines and journals, and it was observed that the knowledge of the patient and his family changed after an intervention based on evidence-based medicine.